2014
DOI: 10.1038/nature13775
|View full text |Cite
|
Sign up to set email alerts
|

Statin treatment rescues FGFR3 skeletal dysplasia phenotypes

Abstract: Gain-of-function mutations in the fibroblast growth factor receptor 3 gene (FGFR3) result in skeletal dysplasias, such as thanatophoric dysplasia and achondroplasia (ACH). The lack of disease models using human cells has hampered the identification of a clinically effective treatment for these diseases. Here we show that statin treatment can rescue patient-specific induced pluripotent stem cell (iPSC) models and a mouse model of FGFR3 skeletal dysplasia. We converted fibroblasts from thanatophoric dysplasia ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
160
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(176 citation statements)
references
References 34 publications
10
160
1
2
Order By: Relevance
“…STAT, MAPK1/3, PI3K-AKT, IHH, PTHLH/PTHrP and BMP are involved in the pathogenesis of chondrodysplasia caused by FGFR3 mutations. 15,53 NPPC (natriuretic peptide C), 54 NPPC analog, 55 FGFR3-binding peptide, 41 PTH, 13 soluble FGFR3 56 and statin 57 were found to partially rescue the retarded bone growth of ACH. While the efficacy and safety of these treatments require further investigation, understanding of more detailed molecular mechanisms will help developing better therapies for achondroplasia.…”
Section: Discussionmentioning
confidence: 99%
“…STAT, MAPK1/3, PI3K-AKT, IHH, PTHLH/PTHrP and BMP are involved in the pathogenesis of chondrodysplasia caused by FGFR3 mutations. 15,53 NPPC (natriuretic peptide C), 54 NPPC analog, 55 FGFR3-binding peptide, 41 PTH, 13 soluble FGFR3 56 and statin 57 were found to partially rescue the retarded bone growth of ACH. While the efficacy and safety of these treatments require further investigation, understanding of more detailed molecular mechanisms will help developing better therapies for achondroplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, questions remain as to whether this is a viable therapeutic option. In a recent article, Yamashita et al (2014) demonstrated that statins could correct the degraded cartilage in both chondrogenically differentiated TDI and ACH induced pluripotent stem cells. Interestingly, mRNA expression levels of FGFR3 were increased by lovastatin, but protein levels by immunoblot decreased, which led the authors to postulate that statins increase the degradation rate of FGFR3 in chondrogenically differentiated TDI induced pluripotent stem cells.…”
Section: C-type Natriuretic Peptide Variant For Fgfr3-related Dwarfismmentioning
confidence: 99%
“…Inhibitory antibodies that specifically target the FGFR3 extracellular domain have been developed as potential cancer therapeutics but have not been evaluated for treatment of achondroplasia (Martinez-Torrecuadrada et al 2005;Hadari and Schlessinger 2009;Qing et al 2009). A recent drug screen of induced pluripotent stem cell-derived chondrocytes from patients with achondroplasia and thanatophoric dysplasia identified statin drugs as effective in improving chondrogenic differentiation in vitro and improving the phenotype (limb and body length) of achondroplasia mice in vivo (Yamashita et al 2014).…”
Section: Therapeutic Strategies In Achondroplasiamentioning
confidence: 99%